Who Is Mr. Science and Why Does He Matter?. Issue 3 (3rd July 2022) - Seow, Victor; Lei, Sean Hsiang-lin
Abstract: This special issue is devoted to exploring the manifestations of Mr. Science in May Fourth China and to examining this icon's significance not only to China's modern era but also to our understandings of science and society beyond. In this introduction, the co-editors make a case for critically engaging Mr. Science and, by extension, questions of science in early twentieth century China, particularly in light of China's emergence as a scientific and technological superpower today—a fact which has, incidentally, been framed by the current PRC government as a realization of May Fourth dreams. In concurrently reinvigorating Mr. Science's idealism, critical edge, and cosmopolitanism while challenging his common association with scientism, the articles in this special issue offer new insights into topics from science and democracy to universality without Eurocentricism, which are of relevance and interest to both modern Chinese history and the global history of science.